Species-Specific Effects of Cation Channel TRPM4 Small-Molecule Inhibitors - Arullampalam, Prakash; Preti, Barbara; Ross-Kaschitza, Daniela; Lochner, Martin; Rougier, Jean-Sébastien; Abriel, Hugues (Frontiers in Pharmacology, 2021)
Background: The Transient Receptor Potential Melastatin member 4 (TRPM4) gene encodes a calcium-activated non-selective cation channel expressed in several tissues. Mutations in TRPM4 have been reported in patients with different types of cardiac conduction defects. It is also linked to immune response and cancers, but the associated molecular mechanisms are still unclear. Thus far, 9-phenanthrol is the most common pharmacological compound used to investigate TRPM4 function. We recently identified two promising aryloxyacyl-anthranilic acid compounds (abbreviated CBA and NBA) inhibiting TRPM4. However, all aforementioned compounds were screened using assays expressing human TRPM4, whereas the efficacy of mouse TRPM4 has not been assessed. Mouse models are essential to investigate ion channel physiology and chemical compound efficacy. Aim: In this study, we performed comparative electrophysiology experiments to assess the effect of these TRPM4 inhibitors on human and mouse TRPM4 channels heterologously expressed in TsA-201 cells. Methods and Results: We identified striking species-dependent differences in TRPM4 responses. NBA inhibited both human and mouse TRPM4 currents when applied intracellularly and extracellularly using excised membrane patches. CBA inhibited human TRPM4, both intracellularly and extracellularly. Unexpectedly, the application of CBA had no inhibiting effect on mouse TRPM4 current when perfused on the extracellular side. Instead, its increased mouse TRPM4 current at negative holding potentials. In addition, CBA on the intracellular side altered the outward rectification component of the mouse TRPM4 current. Application of 9-phenanthrol, both intracellularly and extracellularly, inhibited human TRPM4. For mouse TRPM4, 9-phenanthrol perfusion led to opposite effects depending on the site of application. With intracellular 9-phenanthrol, we observed a tendency towards potentiation of mouse TRPM4 outward current at positive holding potentials. Conclusion: Altogether, these results suggest that pharmacological compounds screened using "humanised assays" should be extensively characterised before application in in vivo mouse models.